Adding Physical Activity Coaching and an Activity Monitor Was No More Effective Than Adding an Attention Control Intervention to Group Exercise for Patients With Chronic Nonspecific Low Back Pain (PAyBACK Trial): A Randomized Trial - Oliveira, Crystian B. [UNESP]; Christofaro, Diego G. D. [UNESP]; Maher, Chris G.; Franco, Márcia R.; Tiedemann, Anne; Silva, Fernanda G.; Damato, Tatiana M. [UNESP]; Nicholas, Michael K.; Pinto, Rafael Z. (Journal of Orthopaedic & Sports Physical Therapy (JOSPT), 2022)
OBJECTIVE: To investigate whether adding physical activity coaching and an activity monitor enhanced the effects of a group exercise program on pain intensity and disability for people with chronic nonspecific low back pain. DESIGN: Randomized controlled trial with concealed allocation, intention-to-treat analysis, and blinding of participants and assessors. METHODS: One hundred sixty participants with chronic nonspecific low back pain who were aged between 18 and 60 years and seeking care at an outpatient physiotherapy clinic participated. Both groups received supervised group exercise therapy. The intervention group also received physical activity coaching sessions aimed at improving physical activity, and physical activity electronic feedback delivered by an activity monitor. The attention control group received modified approaches of coaching sessions and an activity monitor. Disability was measured using the Roland Morris Disability Questionnaire (0-24), and pain intensity was measured using the 11-point Numerical Rating Scale (0-10). Linear mixed models were performed to test for differences between groups. RESULTS: There were no differences between groups for reductions in disability (mean difference [MD] = -0.5 out of 24 points; 95% confidence interval [CI]: -2.2, 1.1) and pain intensity (MD = -0.4 out of 10 points; 95% CI: -1.3, 0.5) at 3-month follow-up. There were no between-groups differences at 6- and 12-month follow-up assessments. CONCLUSION: Adding targeted physical activity coaching and an activity monitor did not reduce pain intensity or disability more than an attention control approach in participants with chronic low back pain who were undertaking a group exercise program.
Keywords: clinical trials/intervention studies; low back/lumbar spine; therapeutic exercise